ALGORITHMIC PROCESSES AND LOGICAL SYSTEMS MODELING IN ANYLOGIC ENVIRONMENT TO OPTIMIZE COMPLEX SYSTEMS - Dilfuza Nishonova (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This paper explores the application of algorithmic processes and logical systems modeling in the AnyLogic environment to optimize complex systems, particularly in the  context  of  education.  The  study  investigates  various  algorithmic  approaches, simulation techniques, and optimization strategies to enhance system performance and decision-making. By analyzing different methodologies, this research aims to highlight the  significance  of  logical  modeling  and  simulation  in  improving  efficiency  and accuracy.  Furthermore,  it  discusses  the  importance  of  integrating  computational algorithms to support intelligent decision-making and process automation.